A niche strategy for geographical indication products, by valorising local resources: the Greek cheese Ladotyri Mytilinis. (5th July 2022) - Spilioti, Maria; Stachtiaris, Spiros; Kominakis, Antonios; Karanikolas, Pavlos; Tsiboukas, Konstantinos
This study aims to develop a niche strategy for the Greek geographical indication (GI) product Ladotyri Mytilinis, through the valorisation of local resources, especially the local livestock breed. The strategy emphasises the quality, production methods, and regional identity of this product. Data were collected through a thorough literature review and field research. The specifications of the product and the valorisation of local resources can utilise the local sheep breed, its nutrition, the habitat in which it lives, the quality of its products, and the breeding system. The product is integrated into markets in multiple ways. The milk of the local breed is used in three different GI products. The governance of this geographical indication is characterised by concentration, lack of coordination and absence of a specialised collective structure. Various elements of value chain governance through contracting, network governance, and informal relationships have been identified.